The Impact of Problem-Based Learning on Religious Poetry Writing Skills Among Senior High School Students - Marini Razanah; Nani Solihati; Zamah Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model on the religious poetry writing skills of tenth-grade high school students. The study used a quasi-experimental pretest–posttest nonequivalent control group design and was conducted in a public high school in the odd semester. The subjects were 60 tenth-grade students who were divided into two groups: the experimental group (PBL; n=30) and the control group (conventional learning; n=30). The main instrument was a religious poetry writing performance test on the pretest and posttest which was assessed using an analytical rubric on a scale of 1–4. Data were analyzed using descriptive statistics (mean±SD), independent t-test for initial equality, paired t-test for changes in groups, and Cohen’s d (within), Hedges’ g (between), and η² (Group×Time) effect sizes. The results showed that the experimental group experienced significant improvements in all indicators (p<0.05) with moderate to large effects, while the control group showed no significant changes (p>0.05). Thus, PBL is more effective than conventional learning in improving the quality of religious poetry of class X students and is recommended for poetry writing learning in high school.